International security : the contemporary agenda - Dannreuther, Roland (Cambridge, UK : Polity, 2013)
International Security is a cutting-edge analysis of the key security challenges and developments in the post-Cold War world. Drawing on a wide range of contemporary examples, from the Iraq war to the rise of China, it is an essential guide for students and policy makers seeking to understand the theoretical and empirical debates over the fast-changing nature of international security today. The book is organized into four main parts. Part 1 provides an analytical framework for the book, identifying the most significant post-Cold War shifts.
Thinking about security after the Cold War -- Theorizing about security after the Cold War -- Understanding contemporary war and insecurity -- Dilemmas and challenges of intervention -- Collective security, alliances and security cooperation -- Environmental security -- The struggle for resources : oil and water -- People on the move : migration as a security issue -- International terrorism and the impact of 9/11 -- Proliferation of weapons of mass destruction -- Cyber-warfare and new spaces of security / (by Jamie Allinson).
Includes bibliographical references (p. 283-323) and index.
Keywords: Security, International